The Impact of Economic Growth, Industrialization, and Population on CO₂ Emissions in ASEAN - Adhy Satya Pratama; Deni Marsha; Aswan Aswan; Kasnawati Kasnawati (Advances in Economics & Financial Studies, 2026)
Purpose: This study examines the effects of economic growth, industrial value added, and population on carbon dioxide emissions in five ASEAN countries and tests the proposed relationships among these variables. Research Method: A quantitative panel-data design was applied to Indonesia, Malaysia, the Philippines, Thailand, and Vietnam during 2015–2024, producing 50 observations. Data were obtained from international databases and analyzed using panel-data regression. The Chow and Hausman tests selected the Fixed Effect Model, supported by normality, heteroscedasticity, and multicollinearity tests. Results and Discussion: Industrial value added positively and significantly affects carbon emissions, with a coefficient of 0.8179 and a p-value of 0.0000. Population also has a positive and significant effect, with a coefficient of 1.5385 and a p-value of 0.0014. Economic growth has no significant effect. The model explains 98.62% of the variation in carbon emissions. These findings show that industrialization and population growth are the main emission drivers in the selected ASEAN countries. Implications: ASEAN governments should promote industrial decarbonization, renewable energy, clean technology, sustainable urban planning, and country-specific environmental policies. Originality: This study provides recent comparative evidence by accounting for country-specific heterogeneity through the Fixed Effect Model.